The Effectiveness of Primary and Secondary Communication in Early Prevention Efforts for Diabetes Mellitus Among Students of Citra Bangsa Mandiri Christian High School - Riwu , Deandra M.; Lerik , M. Dinah Ch.; Berek, Noorce Ch.; Purimahua, Sintha L.; Marni, Marni (Jurnal Pangan Gizi dan Kesehatan, 2026)
Background: Data from the Kupang City Health Office indicates that diabetes is among the top 10 most prevalent diseases in Kupang City, with a continuous increase since 2020, reaching 5,371 cases in 2022. These data highlight the importance of early diabetes prevention efforts. Prevention can be achieved by increasing knowledge individually and in groups through health education using primary communication, or direct face-to-face counseling, and secondary communication, or face-to-face counseling using the online platform Google Meet. Objectives:This study aimed to analyze the effectiveness of primary versus secondary communication in increasing the knowledge of students at Citra Bangsa Mandiri Christian High School regarding early prevention efforts for Diabetes Mellitus. Methods: This research employed a Quasi-Experimental design with a pre-post test two-group design, where students' knowledge levels were measured using questionnaires with a sample of 228 students from Citra Bangsa Mandiri Christian High School. Data analysis involved the Kolmogorov-Smirnov normality test and the Mann-Whitney U test for difference analysis. Results: The analysis results showed a significant difference in knowledge between the intervention groups and the control group, with a p-value of 0.000 (p<0.05). Conclusions: The conclusion is that primary communication was more effective than secondary communication in increasing the knowledge of students at Citra Bangsa Mandiri Christian High School regarding early prevention efforts for diabetes mellitus. Based on these findings, primary communication needs to be prioritized in efforts to increase knowledge. Secondary communication should be used under specific conditions.